O complexo industrial da saúde no território francês: uma análise do circuito espacial produtivo de biomedicamentos - Ricardo Mendes Antas Jr. (Confins)
We approached in this article the production of biomedicines in french territory, and we understand this specialization as a productive space circuit and not as a productive chain.This productive spatial circuit is part of the health industrial complex, a concept that offers a knowledge of the spatial and historical context for the analysis performed. At last, the biomedicines production is treated more specifically on contracts CDMO, which is the medicines manufacture by third parties in the production of state-of-the-art technology to meet the demands of pharmaceutical laboratories, when previously this stage was of its exclusivity.